Bone metastases from malignant melanoma - Brountzos, Elias (Radiology and oncology (Ljubljana), 2001)
Background. The aim of the study was to evaluate the clinical characteristics,the radiological findings, and the treatment effect on the patients with bone metastases from malignant melanoma. Patients and methods. Retrospective review of 293 stage IV melanoma patients during a 15-year periodwas made. Results. Twenty-eight patients (9.5%) with bone metastases were identified; all patients had a thick or intermediate primary melanoma (Breslow 2.7-9.9). Most of the patients presented with multiple (95.6%, symptomatic (92.60 skeletal lesions. Imaging depicted 90 bone lesions. Axial metastases were more common (86%); 54% of them were located at the spine. Skeletal radionuclide scintigraphy was non-specific; radiographic and computedtomography was diagnostic. Typical bone metastases were osteolytic (92.5%). Sixty-six lesions were treated with radiotherapy; in 79% there was a palliative response. There was no correlation between total dose or fraction size and effective palliation. The skeletal lesions did not respond to concurrent chemotherapy and/or biphosphonates. Median response duration to treatment was estimated to 2.6 months and median survival to 4.7 months. Conclusions. Osseous metastases from malignant melanoma occur in the patients with more advanced primary lesions. They are most frequently osteolytic and located in the axial skeleton. Radiographij and computed tomography is diagnostic. Radiotherapy still remains the treatment of choice.
Keywords: Bone neoplasms; diagnostika; kosti; melanom; Melanoma; metastaze; Neoplasm metastasis; Neoplasm staging; Palliative care; Radiography; Radiotherapy; rak (medicina); Secondary; Survival rate; Tomography, x-ray computed